Explanation:
The easiest way to solve this (in my opinion) is to use the Pythagorean theorem
![(-b+-√(b^2-4(a)(c)) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ew7uichub8pa61h6wk2y5unfk736jekpdh.png)
In this case, 5 is a, with the highest power, 13 is b, with the second highest power, and -6 is c, with a 0 power.
Or, looking at this equation
we can gain that knowledge as well.
So let's plug these values in and solve!
![(-b+-√(b^2-4(a)(c)) )/(2a) = (-13+-√(13^2-4(5)(-6)) )/(2(5))\\=(-13+-√(169+120) )/(10)=(-13+-√(289) )/(10)=(-13+-17 )/(10)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cvtz1hfupwmi48lrb2402j50hzoy2yg6wa.png)
Now we simplify this into two different answers, one when we add, and one when we subtract:
![add:(-13+17 )/(10)=(4)/(10)=(2)/(5)\\subtract:(-13-17 )/(10)=(-30 )/(10)=-3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3u253wfr4cdes6alb860hpuf3swaos1zbs.png)
So, assuming the question asked to solve for x (which I'm assuming it did), our answers are x = -3 and
![(2)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t0uv673spbc3c31ajeld1inwaddg10eja3.png)
Answer:
x = -3
x =
![(2)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t0uv673spbc3c31ajeld1inwaddg10eja3.png)